Sport mega-brands : case studies in international marketing / James Santomier - Santomier, James Jr (Faculty of Business and Management ; UiTM Press, 2002)
The complexity of the sport industry, growing interest in sport entertainment, increasing competition, influence of technology, and growing convergence of consumer needs are prompting multinational sport enterprises to leverage brand equity and extend their global reach. This paper examines: 1) sport marketing trends associated with international marketing; 2) vertical integration across the sport industry; and 3) global marketing and branding strategies of selected sport "mega-brands." Findings indicated a high degree of vertical integration across the sport industry and that media transnational corporations (TNCs) are distribution channels for a wide variety of sport entertainment. It was determined that media TNCs acilitate the global marketing and branding strategies of their sport properties as well as other sport enterprises by leveraging synergies in advertising, marketing, program development, Internet resources, sponsorship, and cross-promotion